Presenilin1 FAD mutants impair ischemia‐induced brain neovascularization and neuronal survival decreasing γ‐secretase processing of ephrinB2 and ephrinB2‐mediated angiogenic functions. (1st February 2022) - Georgakopoulos, Anastasios; Yoon, Yonejung; Voloudakis, Georgios; Dimovasili, Christina; Chen, Lei; Tang, Cheuk; Hof, Patrick R; Robakis, Nikolaos K
Abstract: Background: Cerebral microvasculature abnormalities are implicated in Alzheimer's disease (AD) neuropathology. Ischemic lesions causing neuronal damage are often found in AD brains. The brain responds to ischemia by stimulating tissue neovascularization via sprouting angiogenesis, impairment of this function renders the brain vulnerable to the insult. It has been hypothesized that decreased angiogenesis in AD leads to insufficient blood flow and neuronal dysfunction in affected areas. The EphB4/ephrinB2 (efnB2) ligand‐receptor system regulates brain angiogenesis in response to ischemia. Method: To study the EphB4‐induced angiogenic functions of primary cortical endothelial cells (pCEC) we used the in vitro angiogenesis assays: sprouting on beads and tube formation. To analyze the VE‐cadherin angiogenic complexes in pCEC and brain extracts we used co‐immunoprecipitations, western blotting and spPLA. For the in vivo experiments we used kcnockin mice (KI) expressing PS1 FAD mutants and MCAO, MRI and immunohistochemistry of brain sections. The behavioral tests were: Novel object recognition, Ymaze, Open field and Rotarod test. Result: PS1/γ‐secretase regulate EphB4‐induced sprouting, tube formation and VE‐cadherin angiogenic complexes in pCEC and these functions including processing of efnB2 by γ‐secretase are decreased by PS1 FAD mutants. Ischemia stimulates formation of these angiogenic complexes in the brain and this function is attenuated by PS1 FAD mutants together with ischemia‐induced neovascularization and cerebral blood flow while neuronal death and cognitive decline are increased. We finally found that a small peptide, which derives from the product of cleavage of efnB2 by γ‐secretase rescues angiogenic functions of PS1 FAD ECs. Conclusion: Together, our data support the hypothesis that PS1 FAD mutants inhibit ischemia‐induced angiogenic functions of ECs by decreasing the γ‐secretase processing of efnB2 and impairing the EphB4/efnB2 signaling, thus decreasing neovascularization in the brain and leading to increased vulnerability to the insult, cognitive decline and neuronal death. Furthermore, our data reveal a novel brain angiogenic mechanism targeted by PS1 FAD mutants and a potential therapeutic target for ischemia‐induced neurodegeneration. Importantly, FAD mutant effects occur in absence of neuropathological hallmarks of AD, supporting such hallmarks may form downstream of mutant effects on neoangiogenesis and neuronal survival.